PENGEMBANGAN VIDEO PEMBELAJARAN TATA RIAS GERIATRI SEBAGAI MEDIA PEMBELAJARAN SISWA PROGRAM KEAHLIAN KECANIKAN DI SMKN 1 BUDURAN - Dini Murtafi’ah Azmi; Mutimmatul Faidah; Wilujeng, Biyan Yesi; FERNANDA, M.A. Hanny Ferry (Jurnal Tata Rias, 2025)
This research is motivated bythe students need to enhance their interest and learning outcomes in skills aspects. The aim of this research is to develop effective learning media for the learning process in the competency of geriatric facial makeup.Therealityat SMKN 1 Buduran shows a lack of learningmedia facilities toimprove the skills required by the students and that these are not suitable for the characteristics of the students at SMKN 1 Buduran. The main objectives of this research specifically consist of four points: 1) To develop video-based learning media, 2) To assess the feasibility of the developed video learning media, 3) To know the students' responses to the developed learning media, 4) To measure students' learning outcomes in the skills aspect. This research employs the R&D method byBorg and Gall.Theresearch sample consists of 36 students from class XI HD MUA at SMKN 1 Buduran. Data collection was carried out through interviews, feasibility validation tests, student response questionnaires, and performance tests based on performance assessmentrubrics. The feasibility validation score from 3 expertsreceived an average total score of 4.60, which falls into the 'verygood' category. The results from 36 students received positive feedback, resulting in an average total score of 4.65, also falling into the 'very good' category. Student learning outcomes in the skill aspect showed the effectiveness of this media, achieving an average total score of 87.3. Therefore, the development of learning media in this research can be said to be successful in enhancing students' interest and learning outcomes both in a classical and individual manner in the material of geriatric facial makeup competency. Keywords: Learning Video Media, Geriatric Makeup, R&D.